A single step ice accretion model using Level-Set method. (August 2016) - Pena, Dorian; Hoarau, Yannick; Laurendeau, Eric
Abstract: A new approach using the Level-Set framework is developed in the NSMB (Navier–Stokes-multi-block) compressible solver for modeling the ice/air interface evolution through time during in-flight icing. Droplet distribution and impingement efficiency are computed by an Eulerian approach and the accreted ice is calculated by a PDE model. An icing velocity field is introduced and the Level-Set equations are solved on body-fitted multi-block structured grids. The whole process is parallelized with the MPI library for efficient calculations. Single step icing is simulated on NACA23012 and NACA0012 airfoils and on the ONERA-M6 and the GLC-305 swept wings. In all the studied cases, the results are in good agreement with existing and available data validating the feasibility of the approach.